Trimmed Least Square Estimators for Stable Ar(1) Processes - Bazarova, Alina; Berkes, István; Horváth, Lajos (Mathematica Pannonica, 2022)
We prove the weak consistency of the trimmed least square estimator of the covariance parameter of an AR(1) process with stable errors.